NIGERIAN AIRFORCE STRATEGIC DEVELOPMENT AND CAPACITY IN THE FOURTH REPUBLIC, 2019-2023 - EFEFIONG ASUQUO EDET; INAH EMMANUEL MKPE; AKPANKE BETIANG JOSEPH (International Studies Journal)
This study examines the strategic development and capacity of Nigerian Airforce (NAF) in the Fourth Republic, with particular focus from 2015 to 2023. In recent years, the nation has had to contend with threats from armed banditry, kidnapping, separatist armed organizations, and other forms of criminality in addition to terrorism in the Northeast. This situation has preoccupied the national security forces, including the Airforce which has carried out several operations to address these threats. Whereas extant literature on the Nigerian Airforce has documented the history and assessed the challenges of the force, this paper contributes to the literature by examining the trajectory of the force, in terms of strategic development and capacity, during President Buhari’s administration (2015-2023) which was characterized by humongous spending on the security sector amid alarming insecurity. The paper adopted the documentary design. Data was collected from secondary sources and analyzed using the descriptive method. Findings showed that there had been monumental progress during the period under study as government effectively supported the NAF by acquiring more platforms and supervising innovation and advancement in virtually every area of the service. A strategic approach to acquisition and reactivation had allowed the NAF to accrue a substantial number of aircraft and platforms in multiple fleets, quite unmatched in previous years.